PENGARUH KEMAMPUAN LITERASI TERHDAP HASIL BELAJAR BAHASA INDONESIA SISWA - Wulandari Julia Permani; Ida Ermiana; Darmiany (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the influence of students’ literacy skills on their learning outcomes in Indonesian language subjects among fifth- and sixth-grade students at SDN 9 Buwun Mas. Literacy is recognized as a fundamental 21st-century competence that encompasses not only reading and writing but also listening, speaking, analyzing, and critically interpreting information. National and international assessments such as PIRLS, INAP, and PISA consistently show that Indonesian students’ reading literacy remains below global expectations, indicating the need for strengthened literacy practices in schools. SDN 9 Buwun Mas has implemented daily 15-minute reading activities and weekly literacy programs; however, several challenges persist, including students’ boredom, limited book collections, and a lack of public awareness regarding the importance of literacy. These issues are reflected in students’ learning outcomes, which hover only slightly above the minimum competency standards. Using a quantitative correlational design, this study involved 26 students from grades V and VI as research participants. Data were collected through student questionnaires, worksheets, and interviews with classroom teachers. The findings are expected to identify students’ current literacy skills and analyze their influence on Indonesian language learning outcomes. Based on preliminary observations and supporting previous research, it is hypothesized that literacy skills have a positive and significant effect on learning outcomes. The results of this study are expected to provide insights for schools, teachers, and policymakers to improve literacy practices and enhance students’ academic achievement in Indonesian language learning.